The Candidate Schizophrenia Risk Gene Tmem108 Regulates Glucose Metabolism Homeostasis - Yu, Jianbo; Liao, Xufeng; Zhong, Yanzi; Wu, Yongqiang; Lai, Xinsheng; Jiao, Huifeng; Yan, Min; Zhang, Yu; Ma, Chaolin; Wang, Shunqi (Frontiers in Endocrinology, 2021)
Background: Schizophrenia (SCZ) is a severe psychiatric disease affected by genetic factors and environmental contributors, and premorbid abnormality of glucose metabolism is one of the SCZ characteristics supposed to contribute to the disease's pathological process. Transmembrane protein 108 (Tmem108) is a susceptible gene associated with multiple psychiatric diseases, including SCZ. Moreover, Tmem108 mutant mice exhibit SCZ-like behaviors in the measurement of sensorimotor gating. However, it is unknown whether Tmem108 regulates glucose metabolism homeostasis while it involves SCZ pathophysiological process. Results: In this research, we found that Tmem108 mutant mice exhibited glucose intolerance, insulin resistance, and disturbed metabolic homeostasis. Food and oxygen consumption decreased, and urine production increased, accompanied by weak fatigue resistance in the mutant mice. Simultaneously, the glucose metabolic pathway was enhanced, and lipid metabolism decreased in the mutant mice, consistent with the elevated respiratory exchange ratio (RER). Furthermore, metformin attenuated plasma glucose levels and improved sensorimotor gating in Tmem108 mutant mice. Conclusions: Hyperglycemia occurs more often in SCZ patients than in control, implying that these two diseases share common biological mechanisms, here we demonstrate that the Tmem108 mutant may represent such a comorbid mechanism.